The Influence of Knowledge about Islamic Banking on Interest in Saving at Islamic Banks - Mahlil; Patria Yunita; Ahkmad Syafiudin; Aries Muftie (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2024)
This study examined the influence of knowledge about Islamic banking on interest in saving in Islamic banks among active Stebank students who had taken banking courses. Using a quantitative approach and questionnaires, the research found a positive correlation between knowledge of Islamic banking and interest in saving. Higher knowledge, indicated by understanding of Islamic banking facts, led to increased interest in saving in Islamic banks. This finding aligns with previous research and expert opinions, highlighting the importance of knowledge in boosting interest. Students, as potential customers, are crucial for Islamic banks, emphasizing the need to cater to their preferences. This research encourages saving in Islamic banks among students and others, contributing to the growth of Islamic banking. Future studies should explore additional variables to uncover more factors influencing interest in saving in Islamic banks, thereby fostering stronger financial partnerships and further developing Islamic banking in the broader Islamic economy.